Antioxidant Testing of Solid Soap Preparations Containing Ethanol Extract from California Papaya Leaves (Carica Papaya L.) - Gabriela Reyna Rumi; Ratih Arum Astuti; Irwandi Irwandi (Jurnal EduHealth, 2025)
Air pollution is a global environmental problem that is getting worse due to the mixing of natural atmospheric components with pollutants from human and natural activities. One of the main causes of air pollution in Southwest Papua is the increase in the number of motor vehicles, especially in cities such as Sorong, which also contributes to increased pollutant emissions. One plant that has antioxidant activity is papaya, which contains flavonoids, tannins, and alkaloids. Papaya (Carica papaya L) is a fruit from the Caricaceae family. This study aims to test and determine the antioxidant activity in solid soap preparations and preparation concentrations. This study uses two concentrations, namely 8% and 24%. Positive control used quercetin as a comparison. The results of the study conducted on 8% concentration solid soap preparations showed an IC50 value of 37.77, while 24% concentration preparations showed an IC50 value of 36.81. From the results obtained, it can be concluded that California papaya leaf ethanol extract solid soap preparations have high antioxidant activity When compared to the positive control quercetin, the IC₅₀ value of quercetin is 0.93 ppm, meaning that the positive control quercetin has stronger antioxidant activity.